Metaanalyzing Foucault’s Archaeology Theory - Masoud Zare Mehrjardy; Ali Yousofi; Saeideh Mirabi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Foucault’s theoretical foundations have often undergone significant rotations. Foucault’s commentators usually divide his scientific period into the duality of archeology-genealogy or the triad of archeology-genealogy-ethics. In this paper, Foucault’s archeology was analyzed through a meta-theoretical approach based on a combined model. This model is a selection of Ritzer’s meta-theoretical logic (including four external-social, internal-social, external-intellectual, and internal-intellectual approaches) and Chalabi’s conceptual package (including four analytical elements of theory including theory-building equipment, theoretical claims range, theoretical functions, and Theoretical construction). The results show that although archeology is less important to researchers than genealogy; however, in addition to being an efficient theoretical approach to historical, sociological research, it provides a different perspective on society, history, knowledge, and knowledge; It is also a methodological approach with separate guidelines and with a fluid and flexible structure that can be used effectively in dynamic sociological, historical research and make it dynamic. The most important criticisms of archaeology are the neglect of political and historical complexities, the failure of the archaeology of knowledge as the subject of succession to epistemology, and philosophical vacuum and refusal to search for a meaningful source for restoring the scattered historical determination of human.